2014
DOI: 10.1103/physrevb.90.174501
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced self-diffusion of adsorbed methanol in silica aerogel

Abstract: Molecular transport of a two-component system of liquid and vapor in a porous medium can be anomalously increased owing to fast exchange between the two phases. 1 We have investigated this phenomenon measuring the self-diffusion coefficient of methanol adsorbed in a 98% porosity aerogel using nuclear magnetic resonance (NMR) field gradient techniques. We found enhancement of several orders of magnitude from which we determined the ballistic mean-free-path in the vapor phase. We have grown globally uniform anis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…At high pressures the effect of the 4 He adsorbed layer on the 3 He diffusion is not significant and therefore D(P) coincides with that of pure 3 He in the aerogel. Similarly to our result, Lee et al 11 reported the observation of the ''anomalous'' diffusion of methanol in aerogels due to the effect of adsorbed layers in the aerogels at room temperatures. Following ref.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…At high pressures the effect of the 4 He adsorbed layer on the 3 He diffusion is not significant and therefore D(P) coincides with that of pure 3 He in the aerogel. Similarly to our result, Lee et al 11 reported the observation of the ''anomalous'' diffusion of methanol in aerogels due to the effect of adsorbed layers in the aerogels at room temperatures. Following ref.…”
Section: Discussionsupporting
confidence: 69%
“…7) even at very low pressures where diffusion is expected to be strongly anisotropic in the Knudsen regime due to anisotropy of the aerogel. Thus we must conclude that the correctness of the simple models application used by Lee et al 11 and Mueller et al 10 is doubtful. The observed diffusion of 3 He gas in the aerogel is significantly more suppressed by adsorption than expected.…”
Section: à9mentioning
confidence: 99%
See 3 more Smart Citations